EVALUASI VALUE ENGINEERING STRUKTUR ATAS BANGUNAN KPRI RSUD DR. ACHMAD MOCHTAR KOTA BUKITTINGGI - Aidil Firman; Ishak Ishak; Elfania Bastian (Ensiklopedia Research and Community Service Review, 2022)
The Substructure of the building of the Civil Servant Cooperative (KPRI) Regional General Hospital (RSUD) Dr. Achmad Mochtar Bukittinggi City was built based on the Indonesian Loading Regulations for Buildings and Buildings (SNI-1727-2013). The modeling is assisted by the ETABS Version 19 software. The dimensions of column K1 on the ground floor are 50x50 cm, K2 on the 1st floor is 40x40 cm, for column K3 on the 2nd floor and K4 on the 3rd floor with the same dimensions, namely 40x40 cm, and K5 on the roof top that is 30×30. While the dimensions of the block B1 is 50×30 cm, B2 is 40×25 cm and B3 is 30×25cm. The research aims to determine the dimensions and analysis of structural loads as well as the effective value of the building, from the results of structural analysis before and after the application of Value Engineering, it is obtained that it has met the provisions of the Indonesian National Standard, so it is safe and feasible.Keywords:  Superstructure, Value Engineering, ETABS.